Attention allocation to illness‐compatible information discriminates women with active versus weight‐recovered anorexia nervosa. Issue 8 (16th December 2019) - Giel, Katrin E.; Conzelmann, Annette; Renner, Tobias J.; Richter, Tabea; Martin Benito, Sebastian; Zipfel, Stephan; Schag, Kathrin
Abstract: Objective: Biased attention for disorder‐relevant information plays a crucial role in the maintenance of different mental disorders including eating disorders and might be of use to define recovery beyond symptom‐related criteria. Method: We assessed attention deployment using eye tracking in a cued choice viewing paradigm to two different categories of disorder‐relevant stimuli in 24 individuals with acute anorexia nervosa (AN), 20 weight‐recovered individuals with a history of AN (WRAN) and 23 healthy control participants (CG). Picture pairs consisted of a food stimulus or a picture depicting physical activity and a matched control stimulus (household item/physical inactivity). Participants rated the valence of stimuli afterwards. Results: The groups did not differ in initial attention deployment. In later processing stages, AN patients showed a generalized attentional avoidance of food and control pictures as compared to CG, while WRAN individuals were in between. AN patients showed an attentional bias toward physical activity pictures as compared to WRAN individuals, but not the CG. AN individuals rated the food pictures and the pictures showing physical inactivity as less pleasant than the CG, while WRAN individuals were in between. Discussion: Attention deployment is partly changed in WRAN as compared to the acute AN group, especially with regard to a shift away from illness‐compatible stimuli (physical activity), and this might be a useful recovery criterion. Valence rating of food stimuli might be an additional useful tool to distinguish between acutely ill and weight‐recovered individuals. Attentional biases for illness‐compatible stimuli might qualify as a valuable approach to defining recovery in AN.